Hubungan Antara Monotonitas Pekerjaan dengan Stres Kerja pada Operator Crane di Terminal Nilam dan Jamrud Pelabuhan Tanjung Perak - Ismara Nareswari; Noeroel Widajati; Ainayya Rizky Savitri (Universitas Airlangga, 2023)
Background: Work stress can happen to any worker, including crane operators. Monotonous work might cause work stress. Work stress can arise when workers do the same job and do it repeatedly without any variation in their work. Objectives: This study aims to determine whether there is a correlation between work monotony with work stress on crane operators in Nilam and Jamrud Terminals of Tanjung Perak Harbor. Methods: A cross-sectional study design was conducted between February - March 2021. The subjects in this study were 58 crane operators obtained from calculating the Slovin formula. The DASS 42 questionnaires were used in this study and instruments in the Indonesian version were validated. SPSS version 21 was used for descriptive and bivariate analysis in the form of contingency coefficient analysis and Spearman correlation. Results: The results showed that the average age was 38 years old and the average tenure was 6 years. All of the crane operators are male. In this study, it was found that most of the crane operators considered their work monotonous (75,9%). Meanwhile, work stress experienced by crane operators is dominant on a normal scale (34,5%), but other crane operators experience work stress ranging from mild to very heavy. The results also show a correlation between work monotony (r=0.570; p-value=0.000) and work stress on crane operators. Conclusions: There are several causes of work stress. Work monotony might cause work stress. It is important for crane operators to have variation in their job and for company to arrange proper rest time so the crane operators will have enough time to rest after long work hours. In addition, the researcher also suggests to further research to be able to conduct similar research related to other factors that can cause work stress. Variables of work burnout and work variation can be variables that can be considered for further research to determine the relationship with work stress.